Analysis of Mineral Characteristics of Leang Lonrong Cave Ornaments in The Pangkep Karst Area, South Sulawesi, Bantimurung Bulusaraung National Park - Nur Rahmi MS; Muhammad Arsyad; Agus Susanto (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
Research has been carried out on the mineral content of caves in the Leang Lonrong Pangkep Karst Area with experimental research methods. The purposes of this study are to analyze the characteristics of Leang Lonrong Cave, explain the mineral content of the Leang Lonrong Cave ornaments, and show the presence of RRE elements contained in the Leang Lonrong Cave ornaments. The characteristic data of the cave was obtained from direct observations, and measurements in the Leang Lonrong cave in the form of cave dimension data, namely the length of the cave with a size of ±150 meters, the height of the mouth of the cave 1.91 meters and the length of the mouth of the cave 6.40 meters and the intensity of light in the cave obtained 0 lux with a temperature of 26˚ C and 88% humidity. The data were analyzed descriptively and qualitatively using match software, namely X-Ray Diffraction data obtained from sample characterization using X-Ray Diffraction tools on cave ornaments. Dominated by carbon elements marked with white ornaments, the analysis results were obtained. It is known that the mineral content in the cave ornament samples is impure Calcite derived from the dissolution of limestone in karst rocks. From the statement, it is known that each ornament contains Calcite. The results of the descriptive analysis in the form of temperature, humidity, light intensity, fauna and flora, and cave ornaments. The results of the descriptive study in the form of temperature, humidity, light intensity, fauna and flora, and cave ornaments. From the qualitative results obtained, the mineral content of Calcite is the most mineral constituent of cave ornaments, and received rare earth metal elements (RRE) in the minerals of each stalactite ornament in the form of elements Yb (ytterbium), Ce (cerium), and La (Lanthanide)